Management of Tessier Type 3 Cleft With a Novel Reverse Palatal Expander. Issue 8 (November 2021) - Kim, Erinn N.; Moss, Whitney D.; Yamashiro, Duane K.; Tuncer, Fatma B.; Siddiqi, Faizi A.
Abstract : Abstract: The purpose of this clinical report is to present the novel management of a type Tessier 3 cleft which was treated using a palatal expander in reverse fashion to reapproximate the craniofacial skeleton allowing for closure of the palate and soft tissue of the cleft. Reapproximation of the bony component of the cleft was achieved without osteotomies and allowed for easier and earlier realignment of the bony and soft tissue components of the cleft. To our knowledge, this is the first use of reverse palatal expansion in the treatment of type 3 Tessier cleft. Reverse palatal expansion made management of this cleft more straightforward and should be considered as a useful adjunct in the management of wide facial clefts.